The selectivity behaviour of a TADDOL-derived host compound in selected heterocyclic guest solvents - Recchia, Daniella Loridana; Barton, Benita; Hosten, Eric C. (Journal of inclusion phenomena and macrocyclic chemistry, 2025)
TADDOL5 possesses the ability to form complexes with the heterocyclic guest species DIO, PYR, PIP and MOR, and 1:1 (PYR, PIP, MOR) and 2:1 (DIO) H:G inclusion compounds were isolated after host crystallization experiments from these solvents. Guest competition experiments revealed that PIP and MOR were preferred by TADDOL5, while PYR and DIO were less favoured; the selectivity of this host compound for these guests was thus demonstrated to be in the order PIP > MOR > PYR > DIO. SCXRD analyses explained this host preferential order: PIP experienced the shorter and more linear (host)O‒H···N(guest) hydrogen bond with TADDOL5, followed by MOR and PYR. DIO was also retained in the crystal of the complex by means of a hydrogen bond with TADDOL5 of the (host)O‒H···O(guest) type. Hirshfeld surface investigations did not provide further understanding for the host selectivity behaviour when crystallized from mixed guests, but the relative thermal stability of the complex with preferred PIP formed the most stable complex while the inclusion compound with DIO, least favoured, was characterised by the lowest stability. Graphical abstract